Understanding Splenomegaly in Myelofibrosis: Association with Molecular Pathogenesis - Song, Moo-Kon (Int J Mol Sci, 2018)
Myelofibrosis (MF) is a clinical manifestation of chronic BCR-ABL1-negative chronic myeloproliferative neoplasms. Splenomegaly is one of the major clinical manifestations of MF and is directly linked to splenic extramedullary hematopoiesis (EMH). EMH is associated with abnormal trafficking patterns of clonal hematopoietic cells due to the dysregulated bone marrow (BM) microenvironment leading to progressive splenomegaly. Several recent data have emphasized the role of several cytokines for splenic EMH. Alteration of CXCL12/CXCR4 pathway could also lead to splenic EMH by migrated clonal hematopoietic cells from BM to the spleen. Moreover, low Gata1 expression was found to be significantly associated with the EMH. Several gene mutations were found to be associated with significant splenomegaly in MF. In recent data, JAK2 V617F homozygous mutation was associated with a larger spleen size. In other data, CALR mutations in MF were signigicantly associated with longer larger splenomegaly-free survivals than others. In addition, MF patients with ≥1 mutations in AZXL1, EZH1 or IDH1/2 had significantly low spleen reduction response in ruxolitinib treatment. Developments of JAK inhibitors, such as ruxolitinib, pacritinib, momelotinib, and febratinib enabled the effective management in MF patients. Especially, significant spleen reduction responses of the drugs were demonstrated in several randomized clinical studies, although those could not eradicate allele burdens of MF.